Analisis laju korosi logam stainless steel 316l di media air laut menggunakan metode elektrokimia - Alfattah, Muhammad (Journal of New Energies and Manufacturing, 2022)
Indonesia is a country that often experiences tsunami disasters, therefore a tool is needed for early detection of tsunamis, through a technological innovation a tool called inabuoy is created, this inabuoy is an early detection tool for tsunamis that uses sensors under the sea. Inabuoy is placed in the sea where tsunamis often occur. This Ina buoy uses 316L stainless steel as a frame that is submerged in seawater. Because of its position in the sea, corrosion will occur due to immersion in sea water. In this study, 316L stainless steel material will be tested with seawater media and various immersions for 0 hour, 24 hours, 48 hours, 72 hours, and 96 hours using the electrochemical method. This study aims to determine the corrosion rate of stainless steel 316L which was tested in electrochemistry using seawater media and with variations of immersion 0 hour, 24 hours, 48 hours, 72 hours, and 96 hours. After doing the research, the results showed that the corrosion rate showed the lowest corrosion rate occurred in specimens 0 hours of immersion with an average value of 4,5681 x 10-3mmpy while the highest corrosion rate occurred in specimens subjected to 96 hours of immersion, showing an average value of 8,6811 x 10-3 mmpy. From the surface morphology SEM test, it was seen that there were holes that occurred at 0 hours of immersion, namely the formation of black dots and small holes, then at 96 hours of immersion, deep and spread holes were seen on the surface